Communication of Local Farmers’ Products through Facebook: The Case Study of Naše-Vaše - Petriľák, Marek; Janšto, Erik; Horská, Elena (Communication Today, 2020)
Social media are currently not only used for communication between individuals but an increasing number of companies use these means as simple and fast sales and communication channels. The importance of communication with consumers through social networks, such as Facebook, is essential in today’s marketplace for small businesses, for which this tool is one of the cheapest alternatives to communicating and selling products. This trend did not escape agriculture-speciﬁc local farmers who process fresh local products. The study’s objective is to highlight the importance of social media communication in the agri-food sector, speciﬁcally in the sub-sector of local fresh products, as well as to determine which consumers are most interested in local products from farmers communicated through Facebook. We conducted the research using our Facebook page called Ours-Yours (in Slovak Naše-Vaše). This account was created for research purposes and has a clearly deﬁned objective of supporting and promoting local fresh products from small Slovak farmers. Research involved 42 small farms that sell fresh local dairy products. From these farmers we discovered what form of marketing communication they had used in the past. Afterwards, we visited eight selected farms, took professional photos of their products, and promoted them under one brand using our Facebook page Ours-Yours (Naše-Vaše). The methodology of the research was based on an analysis of Facebook posts, which were visualised, uniformly graphically processed photographs of the products. Contributions were advertised on radio located 50 kilometres from the farms to ensure local marketing of the products. We measured demographic factors (gender and age) and users’ interaction with individual posts. Research has shown that women between the ages of 45 – 64, who follow Facebook mostly from their mobile phones, are most interested in Facebook posts with local fresh products (and information about them).